2011
DOI: 10.1002/jcp.22511
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells play a dual role on tumor cell growth in vitro and in vivo

Abstract: Nowadays, some evidences demonstrate that human mesenchymal stem cells (hMSCs) favor tumor growth; however, others show that hMSCs can suppress tumorigenesis and tumor growth. With the indeterminateness of the effect of hMSCs on tumors, we investigated the effect of hMSCs on lung cancer cell line A549 and esophageal cancer cell line Eca-109 in vitro and in vivo. Our results revealed that hMSCs inhibited the proliferation and invasion of A549 and Eca-109 cells, arrested tumor cells in the G1 phase of the cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 30 publications
3
52
0
Order By: Relevance
“…MSCs appear to have a complex biology in other gastrointestinal cancers, including esophageal cancer, gastric cancer, and pancreatic carcinoma. Li et al [77] applied hMSCs together with esophageal cancer cells subcutaneously in nude mice. The authors showed that hMSCs could promote tumor growth with increased tumor vessel formation in vivo.…”
mentioning
confidence: 99%
“…MSCs appear to have a complex biology in other gastrointestinal cancers, including esophageal cancer, gastric cancer, and pancreatic carcinoma. Li et al [77] applied hMSCs together with esophageal cancer cells subcutaneously in nude mice. The authors showed that hMSCs could promote tumor growth with increased tumor vessel formation in vivo.…”
mentioning
confidence: 99%
“…Recently, studies reported that MSCs promote cancer growth and metastasis (20,29). However, MSC cancer-suppressing effects have only been observed in a few reports (33,34); and most studies reported that migration of MSC leads to angiogenesis and tumor development (27,32). Moreover, extensive tropism of BMS cells to tumor was observed, which may be due to the BMS cells secreting a variety of substances such as stem cell factor, interleukins, and colony-stimulating factor-I (5,8).…”
Section: █ Discussionmentioning
confidence: 99%
“…The proposed use of MSCs in cancer therapies provoke strong disagreement in scientific community, due to opposite results for MSC promotion of tumor vascularization, promotion of cancer progression and the invasive tendency of tumors previously reported [28,[120][121][122]. In this contest, Li et al, 2011, inform about the dual role of human MSCs in tumor cell growth in vitro and in vivo. It was found that in vitro human MSCs inhibited the proliferation of A549 (lung cancer) and Eca-109 (esophageal cancer) cell lines and caused G1 phase cell cycle arrest and apoptosis.…”
Section: New Facts Raised Concerns About Use Of Mscs As An Anticancermentioning
confidence: 94%
“…It was found that in vitro human MSCs inhibited the proliferation of A549 (lung cancer) and Eca-109 (esophageal cancer) cell lines and caused G1 phase cell cycle arrest and apoptosis. On the other hand, human MSCs were also found to increase tumor formation and growth in experiments in vivo [123].…”
Section: New Facts Raised Concerns About Use Of Mscs As An Anticancermentioning
confidence: 99%